Effect of miss-distance on the airfoil-vortex interaction. Numerical study - Piechna, J.; Szumowski, A.P. (Archives of Mechanics, 1998)
The effect of a strong vortex interacting with an airfoil flow is investigated numerically. The finite volume method for Euler equations is applied. Instantanous flow patterns, including pressure distributions along the airfoil and lift coefficients, were calculated for various miss-distances of the vortex passing parallel to the airfoil plane. It was found that the effects of interaction are much stronger when the vortex approaching the airfoil accelerates the flow at the pressure surface than in the case when the vortex decelerates the flow at the suction surface.